2018
DOI: 10.1186/s12904-018-0271-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in do-not-resuscitate orders, hospice care utilization, and late referral to hospice care between cancer and non-cancer decedents in a tertiary Hospital in Taiwan between 2010 and 2015: a hospital-based observational study

Abstract: BackgroundIn 2009, the Taiwanese national health insurance system substantially expanded hospice coverage for terminal cancer patients to include patients with end-stage brain, dementia, heart, lung, liver, and kidney diseases. This study aimed to evaluate differences in do-not-resuscitate (DNR) status and hospice care utilization between terminal cancer patients and advanced non-cancer patients after the policy change.MethodsData were obtained from the Death and Hospice Palliative Care Database of Taipei Vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…It has been suggested that palliative care patterns should differ for cancer patients versus non-cancer patients because of distinct disease progression (e.g., steady progression and clear terminal phase for cancer versus gradual decline punctuated by episodes of acute deterioration and more sudden death for respiratory or heart failure [14]. Although palliative care is beneficial for non-cancer patients and their families, the use of palliative care services among noncancer patients is much lower than for cancer patients, and palliative care referral tends to be later [15][16][17][18]. According to the Clinical Practice Research Datalink in England, in 2009, only 234 (7%) of 3122 patients with heart failure were given palliative care by family physicians or referred to special palliative care services, compared to 3669 (48%) of 7608 cancer patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that palliative care patterns should differ for cancer patients versus non-cancer patients because of distinct disease progression (e.g., steady progression and clear terminal phase for cancer versus gradual decline punctuated by episodes of acute deterioration and more sudden death for respiratory or heart failure [14]. Although palliative care is beneficial for non-cancer patients and their families, the use of palliative care services among noncancer patients is much lower than for cancer patients, and palliative care referral tends to be later [15][16][17][18]. According to the Clinical Practice Research Datalink in England, in 2009, only 234 (7%) of 3122 patients with heart failure were given palliative care by family physicians or referred to special palliative care services, compared to 3669 (48%) of 7608 cancer patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, 83.7% to 85.7% of our participants issued a DNR order before death, close to the worldwide predeath prevalence of DNR orders for patients with cancer: 86% reported in the United States, 9 92% in Canada, 10 76% in Korea, 46 74.7% 11 to 80.0% 12 in China, and 94.9% in Taiwan. 13 Discrepancies between DNR orders issued at hospital admission, 8,9,17 for outpatients, 28 or at enrollment in our study and at death reflect lost opportunities to identify a DNR preference due to physicians' insufficiencies in addressing patients' CPR preferences and inadequate patient engagement, as reported by El-Jawahri et al, 8 highlighting the need for effective interventions to identify the CPR preferences of patients with cancer and to facilitate issuance of DNR orders. Although our ACP intervention did not strongly facilitate the overall prevalence of issuing a DNR order before death, as reported, 34,35 it effectively promoted DNR order issuance by helping patients with advanced cancer to develop accurate PA (Table 2), especially among those first reporting accurate PA 31 to 90 days before death (Table 3).…”
Section: Discussionmentioning
confidence: 61%
“…The median time proximities to death since our participants issued a DNR were longer than those reported in the United States (1 day) 9 and China (1 day) 11,12 but comparable to those reported in Canada (6 days) 10 and Taiwan (7 days). 13 Correspondingly, 20.7% to 26.2% and 35.9% to 38.1% of our participants ordered a DNR on the day of death and within 3 days of death, respectively, comparable to or better than reported prevalences: ,26% in Canada, 10 28.1% in Korea, 14 and 41.1% in China 12 on the day of death and 64.7% in Korea 14 and 81.9% in China 12 within 3 days of death. Our findings and those in the literature regarding the time proximity between issuing a DNR order and death signal that physician-patient EoL care communication is delayed and suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that the hospice palliative care enrollment rates of noncancer patients remained substantially lower than those of cancer patients 14 .…”
mentioning
confidence: 87%